DEPTOR inhibits cell proliferation and confers sensitivity to dopamine agonist in pituitary adenoma. (10th September 2019) - Yao, Hong; Tang, Hao; Zhang, Yong; Zhang, Qiu Fen; Liu, Xin Yi; Liu, Yan Ting; Gu, Wei Ting; Zheng, Yong Zhi; Shang, Han Bing; Wang, Yu; Huang, Jin Yan; Wei, Yong Xu; et al.
Abstract: DEP domain-containing mechanistic target of rapamycin (mTOR)-interacting protein (DEPTOR) is an important modulator of mTOR, a highly conserved kinase whose hyperactivation is critically involved in a variety of human tumors. The role of DEPTOR playing in pituitary adenoma (PA) is largely unknown. Here, we reported that DEPTOR was downregulated in PA tissues, especially dopamine-resistant prolactinomas. Consistently, overexpression of DEPTOR inhibited pituitary tumor GH3 and MMQ cells proliferation in vitro and in vivo, and sensitized GH3 and MMQ cells to cabergoline (CAB), a dopamine agonist (DA). Conversely, knockdown of DEPTOR promoted GH3 and MMQ cells proliferation, and conferred cells resistance to CAB. Mechanistically, DEPTOR inhibited both mTOR Complex 1 (mTORC1) and 2 (mTORC2) activities in PA cells. In addition, DEPTOR expression level was increased to suppress mTOR kinase activity via decreasing E3 ubiquitin ligase, βTrCP1, in response to CAB. Furthermore, DEPTOR enhanced autophagy-dependent cell death to confer cells sensitivity to CAB. Taken together, our results suggest that DEPTOR may be a potential target for the treatment of PAs. Highlights: Low DEPTOR expression was positively correlated with pituitary adenomas progression and drug resistance. The ectopic expression of DEPTOR inhibited pituitary adenoma cells proliferation by inactivation of mTOR kinase. DEPTOR conferred GH3 and MMQ cells sensitivity to cabergoline by enhancing autophagy-dependent cell death. DEPTOR may be a promising target for the treatment of pituitary adenomas.